2009
DOI: 10.1158/0008-5472.can-08-2466
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA Mutations in Colorectal Cancer Are Associated with Clinical Resistance to EGFR-Targeted Monoclonal Antibodies

Abstract: The monoclonal antibodies (moAb) panitumumab and cetuximab target the epidermal growth factor receptor (EGFR) and have proven valuable for the treatment of metastatic colorectal cancer (mCRC). EGFR-mediated signaling involves two main intracellular cascades: on one side KRAS activates BRAF, which in turn triggers the mitogen-activated protein kinases. On the other, membrane localization of the lipid kinase PIK3CA counteracts PTEN and promotes AKT1 phosphorylation, thereby activating a parallel intracellular ax… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
483
9
7

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 699 publications
(516 citation statements)
references
References 22 publications
17
483
9
7
Order By: Relevance
“…[38][39][40] Mutations in KRAS or PIK3CA are associated with nonresponsiveness to anti-EGFR therapy. 41,42 Our study indicated that in the case of serous cystic neoplasms, overexpression of the EGFR protein with increased copy number of EGFR transcripts occurs without amplification of the EGFR gene. The serous cystic neoplasms did not show any mutations in exons 18-23 of EGFR, which encode the kinase domain, nor in any of the examined hot spots in KRAS, BRAF, or PIK3CA.…”
Section: Discussionmentioning
confidence: 69%
“…[38][39][40] Mutations in KRAS or PIK3CA are associated with nonresponsiveness to anti-EGFR therapy. 41,42 Our study indicated that in the case of serous cystic neoplasms, overexpression of the EGFR protein with increased copy number of EGFR transcripts occurs without amplification of the EGFR gene. The serous cystic neoplasms did not show any mutations in exons 18-23 of EGFR, which encode the kinase domain, nor in any of the examined hot spots in KRAS, BRAF, or PIK3CA.…”
Section: Discussionmentioning
confidence: 69%
“…In a series of 110 patients treated with cetuximab or panitumumab, Sartore-Bianchi et al (2009) showed that exons 9 and 20 PIK3CA mutations (found in 13.6% of the cases) were correlated with the lack of response to anti-EGFR antibody in multivariate analysis after adjustment for KRAS mutation and PTEN loss of expression (odds ratio ¼ 0.11; 95% CI: 0.00-0.85; P ¼ 0.033). This was also confirmed when only KRAS wild-type patients were analysed.…”
Section: Pik3ca Mutations and Loss Of Pten Expressionmentioning
confidence: 99%
“…The loss of PTEN protein expression (30% of colorectal tumours) may therefore be an additional factor of PI3K/AKT pathway activation, which may be responsible for resistance to anti-EGFR antibodies, as it was firstly reported in a small series of 27 patients in which PTEN protein expression was evaluated by immunohistochemistry (Frattini et al, 2007). However, subsequent studies have reported discrepant results on the predictive value of loss of PTEN expression (Razis et al, 2008;LaurentPuig et al, 2009;Sartore-Bianchi et al, 2009;Loupakis et al, 2009a), in part, due to the use of different methods for the determination of PTEN status and to the absence of standardization of immunohistochemistry. These findings show that, as for PIK3CA mutations, loss of PTEN expression cannot be currently used as a single marker for prediction of resistance to cetuximab in mCRC patients.…”
Section: Pik3ca Mutations and Loss Of Pten Expressionmentioning
confidence: 99%
“…18 KRAS is a proto-oncogene encoding a small 21kD guanosine triphosphate (GTP)/guanosine diphosphate (GDP) binding protein involved in the regulation of cellular response to many extracellular stimuli. 19 After binding and activation by GTP, RAS recruits the oncogene RAF, which phosphorylates MAP2K (mitogen-activated protein kinase kinase), initiating the MAPK signaling leading to the expression of the protein involved in cell proliferation, differentiation and survival.…”
Section: Biomarkers Downstream To Egfrmentioning
confidence: 99%
“…These studies suggest that combining mutation analysis for K-RAS and PIK3CA (loss of PTEN and/or PIK3CA mutation) could identify up to 70% of patients with metastatic colorectal cancer who are unlikely to respond to treatment with an EGFR-targeted monoclonal antibody. 18 …”
Section: Pten-pi3k-akt-mtor Pathway Alterationsmentioning
confidence: 99%